Analysis Of Consumer Satisfaction Medited Purchase Decisions at Counter Veve Acesoris In Baureno Bojonegoro - Abid Muhtarom; Yenni Vera Fibrianti; Sabilar Rosyad; Miftakul Fatoni (Jurnal Sains Sosio Humaniora, 2022)
Counter accessories Veve Baureno Bojonegoro PLS research. This research is quantitative descriptive. This study involved 150 veve accessories Baureno customers during the last 3 months. Sem with smart pls 3.3.7 is used to analyze. Outside, inside, mediation, and Hypothesis testing were used. According to the research, price influences purchasing decisions positively but not significantly. Service quality has little influence on purchasing decisions. Impulse buying affects purchasing decisions positively. Mount's Word positively influences Purchase Decisions(Chuang and Oliva, 2018). Price affects customer satisfaction positively. Service quality increases customer satisfaction. Impulse buying increases customer satisfaction. Mountain consumer satisfaction increases. Satisfaction positively affects purchasing decisions.